2020
DOI: 10.1038/s41598-020-73525-y
|View full text |Cite
|
Sign up to set email alerts
|

The actual 5-year survivors of pancreatic ductal adenocarcinoma based on real-world data

Abstract: Survival data for pancreatic cancer are usually based on actuarial calculations and actual long-term survival rates are rarely reported. Here we use population-level data from the Surveillance, Epidemiology, and End Results program for patients with microscopically confirmed pancreatic ductal adenocarcinoma diagnosed from 1975 to 2011. A total of 84,275 patients with at least 5 years of follow-up were evaluated (follow-up cutoff date: December 31, 2016). Actual 5-year survival for pancreatic cancer increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
197
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(202 citation statements)
references
References 36 publications
5
197
0
Order By: Relevance
“…After diagnosis, the overall survival ranges between four and six months, with a five-year survival rate of <5%. However, survival is significantly higher in early stage disease (IA: 31.7%; IB: 11.8%) compared to more advanced stages (IIA: 9.0%; IIB: 8.7%; III: 1.9%; IV: 0.5%) [ 6 ]. This survival disparity, even in early stages (IA vs IB) makes early diagnosis one of the most important aspects in the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…After diagnosis, the overall survival ranges between four and six months, with a five-year survival rate of <5%. However, survival is significantly higher in early stage disease (IA: 31.7%; IB: 11.8%) compared to more advanced stages (IIA: 9.0%; IIB: 8.7%; III: 1.9%; IV: 0.5%) [ 6 ]. This survival disparity, even in early stages (IA vs IB) makes early diagnosis one of the most important aspects in the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma is a highly aggressive tumor type with a 5-year survival rate below 5% [ 1 ]. It currently ranks as the third leading cause of cancer-mortality, but is expected to become the second leading cause in the U.S.A. by 2030 [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the 5-year OS would significantly reduce to a dismal 3% with distant metastasis. 2 , 3 Several studies have shown that the 5-year OS of resected PDAC patients ranges from 8.1% to 30.7%. 4–6 The significant differences of the 5-year OS between resectable PDAC and PDAC of all stages demonstrated even a poorer prognosis for the 5-year OS of unresectable PDAC patients.…”
Section: Introductionmentioning
confidence: 99%